When Firms Change DirectionWhen Firms Change Direction, by HuffAnne S., HuffJames O., and BarrPamela S.. New York: Oxford University Press, 2001. - Kraatz, Matthew S. (Academy of Management Review, 2002)
The article reviews the book “When Firms Change Direction,” by Anne S. Huff, James O. Huff, and Pamela S. Barr.